POLA ORDINANSI KOMUNITAS POHON DI HUTAN SEKUNDER DISTRIK MANOKWARI UTARA KABUPATEN MANOKWARI - INAREN MARKUS HUBY; JIMMY F. WANMA; MARIANA H. PEDAY (Fakultas Kehutanan UNIPA, 2020)
This study aimed to reveal indicator plant species in the secondary forest by applying a descriptive approach and field observation as well as refer to releve method. Tral vegetation data of vascular plant at seedlings, saplings, poles, and tree stages that analyzed using MVA.4 (TWINSPAN) software. The analyzed result indicated 12 groups of associations and 1 group of solitary association in which the species were categorized as dominant. The most often appear species in 12 association group based on their growing shapes were Actinodaphne nitida, Celtis latifolia, Hemappasandra sp., Teijmaniodendron sp., Lea acuelata, Spatiostemon jevensis, Koordersiodendron pinnatum, Sisipus sp., Sterculia macrophylla, Litsea timoriana, Macaranga sp., Aglaia sp., Rhus taitensis, Alstonia scholaris, Archidendron parviflorum, Callophylum inophylum and Ficus sp. While the most dominant species in the solitary association were Chisocheton ceremicus, Cryptocarya sp., Canarium hirsutum, Euodia elleryana, Litsea ladermani, and Litsea timoriana. These species arranged and functioned as the dominant tree structure in the secondary forest along the north Manokwari area of Manokwari.